Manufacture and characterisation of porous phosphate, borate and silicate glass microspheres for biomedical applications - Islam, Md Towhidul (2019)
There is a growing trend to develop bioactive materials with enhanced properties for use in biomedical applications especially for bone repair. Ideally, these materials would stimulate a beneficial tissue response, enhance new tissue formation. Microspheres are emerging as potential advanced materials and have been a significant focus of attention due to their advantageous properties over other particle geometries. For example, particles with spherical morphology can provide the advantage of uniformity in size and shape and are easier to deliver to the target tissue site due to their enhanced flow properties. Furthermore, microspheres can be implemented in defect areas more compactly if bimodal distribution of particle sizes are employed. Initially, the focus of this project was on phosphate-based glasses (PBG’s) and novel formulation development (and their characterisation). The second part of this work involved manufacture of both solid and more uniquely porous microspheres from all three glass families (i.e. phosphate, borate and silicate). A series of PBG’s were prepared and their physico-chemical and structural characteristics investigated. Varying formulations in the glass system of 40P2O5-(24-x)MgO-(16+x)CaO-(20-y)Na2O-yTiO2 (where 0≤x≤22 and y=0 or 1) were prepared via melt-quenching. The structure of the glasses was confirmed by X-ray diffraction (XRD), Fourier transform infrared (FTIR), micro Raman and solid-state nuclear magnetic resonance (NMR) spectroscopies. The thermal properties and the activation energy of crystallisation (Ec) were measured using thermal analysis and the Kissinger equation, respectively. For the bulk glass materials characterisation, the glass forming ability of the formulations investigated was seen to decrease with reducing MgO content down to 8 mol% and the glass stability region also decreased from 106 °C to 90 °C with decreasing MgO content. The activation energy of crystallisation (Ec) values also decreased from 248 (for 24 mol% MgO glass) to 229 kJ/mol (for the 8 mol% MgO content) with the replacement of MgO by CaO for glasses with no TiO2. The formulations containing less than 8 mol% MgO without TiO2 showed a strong tendency towards crystallisation. However, addition of 1 mol% TiO2 in place of Na2O for these glasses with less than 8 mol% MgO content, inhibited their crystallisation tendency. Glasses containing 8 mol% MgO with 1 mol% TiO2 revealed a 12 °C higher glass transition temperature, a 14 °C increase in glass stability against crystallisation and a 38 kJ/mol increase in Ec in comparison to their non TiO2 containing counterpart. NMR spectroscopy revealed that all of the formulations contained almost equal percentages of Q1 and Q2 species. However, FTIR and Raman spectroscopies showed that the local structure of the glasses had been altered with addition of 1 mol% TiO2, which acted as a network modifier, impeding crystallisation by increasing the cross-linking between phosphate chains and consequently leading to increased Ec as well as their glass forming ability. Degradation studies of phosphate based glass discs were performed in phosphate buffered saline (PBS) at 37 °C, where the 8 mol% MgO glass showed the highest mass loss of around 3.4% after 28 days of immersion. Cation and anion release studies were conducted via ion chromatography and inductively coupled plasma mass spectroscopy (ICP-MS), respectively, using ultra-pure (Milli-Q) water at 37 °C as the degradation medium. The largest release of Ca, Na and P ions was observed with the 8 mol% MgO glass. In vitro CaP formation studies were conducted using glass discs immersed in simulated body fluid (SBF) at 37 °C for up to 28 days. The amorphous phase and chemical composition of deposited calcium phosphate layers on the glass discs were confirmed via X-ray Diffraction (XRD) and energy-dispersive X-ray spectroscopy (EDX) analysis, respectively. CaP layers with Ca/P ratio 0.8 to 1.1 were found to be deposited on the lower MgO content (8 to 2 mol%) glass surface after 28 days of SBF study. The microsphere development studies showed successful manufacture of both solid and highly porous phosphate, borate and bio-silicate glass microspheres with porosity levels up to 78% with a surface area of 0.4345 m2/g and high levels of interconnectivity. Thermal, degradation, ion release and in vitro bioactivity study of microspheres were also conducted. Dissolution studies showed that the higher mass loss was observed for porous glass microspheres (PGMS) in comparison to their respective solid glass microspheres (SGMS) due to the higher surface area for PGMS. Other than phosphate glass microspheres, both solid and porous glass microspheres of borate and silicate glasses showed bioactivity in simulated body fluid. PGMS of borate and silicate formed hydroxyapatite at earlier time point compared to their respective SGMS. Moreover, porous borate glass microspheres were fully converted into HA porous microspheres in phosphate solutions. However, only amorphous calcium phosphate (a precursor to HA) was found deposited on the surface of porous phosphate glass microspheres after 28 days of immersion in SBF.